A Matter of Control: Colonial and Humanitarian Population Management Strategies, Angolan Refugees’ Resistance, and the Politics of Difference (1961-1964) - Guardião,Ana (2021)
Abstract This article analyses international humanitarian population management strategies deployed in response to the Angolan refugee crisis in the Congo-Leopoldville in the first years of the decolonization war. It contends that the implemented strategies derived from humanitarian organizations’ limitations in adapting to sub-Saharan contexts and were based primarily on host-state needs rather than on refugees’ claims, reflecting, in turn, a shift from a legalistic to a developmental approach in humanitarian assistance. Decolonization specificities and refugee protests were also disregarded in this context, contributing both to the failure of humanitarian population management policies and an extension of the politics of difference from the imperial to the humanitarian realm.